The challenges faced by visual impairments in buying clothes and how to wear clothes / Khairi Asyraf Abdul Karim - Abdul Karim, Khairi Asyraf (Universiti Teknologi MARA, Perak, 2020)
The basis of this project is to make clothing tags using an appropriate font with a braille touch that is specially designed with complete clothing details and a guide to wearing clothes. The purpose of this study is to overcome the challenges of buying and wearing clothing. This study was conducted with an interview method that focuses on the target age range 25 to 35 years in the area of Brickfields, Kuala Lumpur.